Legal Protection Of Children As Perpetrators Of Criminal Acts In The Indonesian Juvenile Justice System - Muhammad Riduan; Syaiful Asmi Hasibuan (ASIAN PUBLISHER, 2023)
Child protection is an important thing that must be done by the state and society. The forms of child protection are carried out from all aspects, starting from guidance to the family, social control of children's socialization and proper handling through regulations made by the State. Juvenile offenses are crimes committed by children. Juvenile crime can be associated with the term